Odpowiedź :
a]
[tex]A=(1,3) \ i \ B=(-4,2)\\\\\{a+b=3\\\{-4a+b=2 \ \ |\cdot(-1)\\\\\{a+b=3\\+\{4a-b=-2\\--------\\\\5a=1 \ \ |:5\\\\a=0,2\\\\0,2+b=3\\\\b=2,8\\\\\huge\boxed{y=0,2x+2,8}[/tex]
a = 0,2 > 0 ⇒ funkcja rosnąca
b]
[tex]C=(-3,0) \ i \ D=(0,4)\\\\\{-3a+b=0\\\{b=4\\\\\{b=4\\\{-3a+4=0\\\\\{b=4\\\{-3a=-4\\\\\{a=\frac{4}{3}\\\{b=4\\\\\huge\boxed{y=\frac{4}{3}x+4}[/tex]
a = 4/3 > 0 ⇒ funkcja rosnąca
c]
[tex]A=(-3,3) \ i \ B=(-3,\frac{1}{5})\\\\\{-3a+b=3\\\{-3a+b=0,2 \ \ |\cdot(-1)\\\\\{-3a+b=3\\+\{3a-b=-0,2\\--------\\\\0=2,8[/tex]
Układ sprzeczny, nie istnieje funkcja, która przechodzi przez podane punkty